On Economic Change: Landmarks Of Economic Modernism : Array - Bodea, Gabriela; Plopeanu, Aurelian-Petruș; Homocianu, Daniel (EuroEconomica, 2020)
Change consists in a noticeable transformation in time, which affects the structure or functioning of the social organization of a community, changing the course of its history. Without being allowed to induce delusions, change imposes development examples for our society, taking on the role of a modernizing agent. The purpose of the present paper is to provide an overview on the process of social modernization via economic, social, cultural and political structures of human communities and government forms, concluding with the fact that modernism is the movement that sets modernization in motion. Our conclusion is that modernism tries to “mask” decadence through innovation, but also taking into account ‘traditional’ as a reality and not disadvantage. Innovation is necessary as well in order to overcome limits of our past, but it cannot cancel traditions and neither does it have the moral rights to do so.